Learning Model Products: Is It Valid? (Study on Geometry Learning Model) - Wardhani, Indah Setyo (Universitas Trunojoyo Madura, 2024)
The learning model was developed to answer the issue of solving learning problems. At elementary school level, one of the models that has been developed is a geometry learning model, such as a spatial imaginative learning model with learning syntax in the form of introduction, demonstration of spatial concepts, facilitation of spatial activities and closing. The learning model syntax will work well if it is equipped with learning model products such as model books, teaching modules, student worksheets, teacher books, etc. To obtain validity and answer whether the product model has valid criteria or not, a validation sheet needs to be developed. The aim of this research is to develop a validation sheet for the learning model product. This research is development research using the Plomp model. The development stages of Plomp are: initial investigation, prototype development, and assessment. The results of the research are in the form of a learning model product validation sheet format. The implication of the research results is the applicability of the learning model product validation sheet format as a tool for obtaining the validity of the learning model product.